Portuguese Advance Directives-a twist against futility? A cross sectional study - Martins, Catarina Sampaio; Nunes, Rui (São Paulo Medical Journal, 2025)
BACKGROUND: Advance Directive documents allow citizens to choose the treatments they want for end-of-life care without considering therapeutic futility. OBJECTIVES: To analyze patients’ and caregivers’ answers to Advance Directives and understand their expectations regarding their decisions. DESIGN AND SETTING: This study analyzed participants’ answers to a previously published trial, conceived to test the document’s efficacy as a communication tool. METHODS: Sixty palliative patients and 60 caregivers (n = 120) registered their preferences in the Advance Directive document and expressed their expectations regarding whether to receive the chosen treatments. RESULTS: In the patient and caregiver groups, 30% and 23.3% wanted to receive cardiorespiratory resuscitation; 23.3% and 25% wanted to receive artificial organ support; and 40% and 35% chose to receive artificial feeding and hydration, respectively. The participants ignored the concept of therapeutic futility and expected to receive invasive treatments. The concept of therapeutic futility should be addressed and discussed with both the patients and caregivers. Legal Advanced Directive documents should be made clear to reduce misinterpretations and potential legal conflicts. CONCLUSION: The authors suggest that all citizens should be clarified regarding the futility concept before filling out the Advance Directives and propose a grammatical change in the document, replacing the phrase “Health Care to Receive / Not to Receive” with the sentence “Health Care to Accept / Refuse” so that patients cannot demand treatments, but instead accept or refuse the proposed therapeutic plans. TRIAL REGISTRATION: ClinicalTrials.gov ID NCT05090072 URL: https://clinicaltrials.gov/ct2/show/NCT05090072.